Iklan Dalam Perspektif Moral Gereja Katolik - Ketupapa, Ferdinandus Natalius Pati (Perspektif, 2016)
Currently, along with the progress of information technology, we find everywhere advertisements: whether on the roads, at workplaces, schools, or at homes. The images of the advertisements that we see may remain in our subconscious and they unconsciously and gently “persuade” us to take up their messages. They could have good effects if their messages conveythe common good. On the contrary, they could cause bad effects since their messages imply certain interests of particular destructive groups. As human creatures who have free will, we can choose not to let our desires be the sort of “game” of those who produce advertisements or choose to conform freely our greed.